Moldova : a Romanian province under Russian rule : diplomatic history from the archives of the great powers - Mitrasca, Marcel (Algora Pub., 2002)
With the Cold War era behind us, the murky territorial questions on Romania's northeastern border start to receive more attention. What are Moldova, Moldavia, Bessarabia, and Transdniestria; and how did they wind up suspended between Romania and Russia? With Wilson's famous 14 points, after the First World War, the nationality principle was first upheld as the basis for the creation of new states and for re-combining portions of existing states. How did the interpretation of the principle change in the ensuing years; how consistently was it applied; and in whose interests? This book analyzes the problem of the Bessarabian Treaty, and offers a glimpse of Romanian foreign policy in the 1920s. Under that Treaty, the de facto unification of Bessarabia with Romania was officially recognized - a great success for Romania. Why, then, did that territory end up under Soviet control (in the "Republic of Moldavia")? Marcel Mitrasca has sifted through unpublished documents from the national archives of Japan, Romania, Great Britain, France and Italy, and presents excerpts to back up his analysis of diplomatic maneuvering between the World Wars. What could Romania's territorial refinements have mattered to Japan? What was Italy's interest? And why was the United States the only Great Power to steadfastly refuse to acknowledge Bessarabia's union with Romania? Mitrasca pieces together the evidence, analyzing the overt and covert negotiations at the Paris Peace Conference and in embassies around the world, and traces the evolving situation that in the end produced a result quite different from what was apparently intended in 1920. While addressed mainly to historians and researchers of diplomatic history, the book offers an extraordinary insight into the treacherous chemistry of global politics, where the destiny of smaller countries is merely the precipitate of Great Power experiments